KOMUNIKASI KELUARGA DALAM PEMAKNAAN INSECURE PADA DIRI REMAJA AKHIR - Khairiyyah, Lathifah; Rina, Nofha (Linimasa : Jurnal Ilmu Komunikasi, 2024)
ABSTRACT   The phenomenon of insecurity is being felt by late adolescents today, because at this age adolescents are experiencing many new phases in life before heading into adulthood. At this age, a lot of worries arise in late adolescents, so that positive family communication is needed to be able to help reduce the feelings of insecurity they are experiencing. This study focuses on the meaning of insecurity in late adolescents in family communication in the city of Bandung, using a descriptive qualitative research method. Data collection techniques used in this research were literature study, observation, and interviews with seven informants, namely three key informants, three supporting informants, and one expert informant. The results of this study indicate that late adolescents interpret insecurity as feeling insecure and insecure, this was found from personal experience and also consultation with a psychologist. Based on the results of interviews, experiences of failure or rejection, social anxiety, and encouragement of perfectionism make late adolescents feel unappreciated or demeaned. Where this will make the late teens become insecure. This research is expected to be useful for late adolescents who experience insecurity in family communication. Keywords: insecure, late adolescents, family communication